Strengthening China's and India's Trade and Investment Ties to the Middle East and North Africa - Pigato, Miria (World Bank, 2012)
The spectacular economic rise of China and India over the past two decades has accelerated their trade with Africa, Latin America, and the Middle East and North Africa (MENA). Their demands for oil, gas, and other natural resources have been driving new relationships with MENA countries based not only on energy but also on trade, investment, and political ties. Indeed, Dubai has become the center of a new Silk Road, the intersection where people, capital, and ideas meet. And while the financial crisis that hit global markets in 2008 has placed downward pressure on growth, these new relationships are likely to deepen in the coming years. The report's main messages are as follows: a) demand for energy from China and India is expected to increase substantially in the future, thus greatly benefiting oil producing countries in the MENA region; b) the oil exporters in the Gulf have laid big bets on economic diversification and knowledge enterprises, bets they might win, but with lots of risk along the way. Oil price volatility may threaten the sustainability of the recent expansion; and c) the growth of China and India offers new market opportunities for the countries in MENA. Besides energy, potential opportunities, for fertilizers, petrochemicals, crude materials, agricultural products, and a number of manufactured goods where MENA has strong comparative advantages, remain unexploited.